2002
DOI: 10.1097/01.asn.0000030392.19694.9d
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Pkhd1, the Mouse Orthologue of the Human ARPKD Gene

Abstract: Abstract. PKHD1, the gene mutated in human autosomal recessive polycystic kidney disease has recently been identified. Its translation products are predicted to belong to a superfamily of proteins involved in the regulation of cellular adhesion and repulsion. One notable aspect of the gene is its unusually complex pattern of splicing. This study shows that mouse Pkhd1 and its translation products have very similar properties to its human orthologue. Mouse Pkhd1 extends over approximately 500 kb of genomic DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
121
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 21 publications
9
121
1
Order By: Relevance
“…We previously characterized the murine Pkhd1 gene and performed detailed expression analyses in embryonic and adult tissues. 9 This study also provided evidence that differentially spliced Pkhd1 mRNAs are expressed in a tissuespecific manner. Because analyses by multiple tissue Northern blots and in situ hybridization indicated that our probe for exon 40 (homologous to exon 41 of the human gene) hybridized with the largest, most abundant transcripts in liver and kidney and also with differentially spliced smaller transcripts in testis, we decided to disrupt exon 40 by insertion of a LacZ-PGK-neo selection cassette (Fig.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…We previously characterized the murine Pkhd1 gene and performed detailed expression analyses in embryonic and adult tissues. 9 This study also provided evidence that differentially spliced Pkhd1 mRNAs are expressed in a tissuespecific manner. Because analyses by multiple tissue Northern blots and in situ hybridization indicated that our probe for exon 40 (homologous to exon 41 of the human gene) hybridized with the largest, most abundant transcripts in liver and kidney and also with differentially spliced smaller transcripts in testis, we decided to disrupt exon 40 by insertion of a LacZ-PGK-neo selection cassette (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…We previously observed the highest levels of Pkhd1 mRNA expression in kidney and lower levels in liver. 9 Northern blot hybridization using exon 40 as a probe and RT-PCR amplification using an exon 40 primer pair failed to detect Pkhd1 mRNA expression in kidney and liver of homozygous mutants (Fig. 1C,E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with our previous report 31 and indicate that FPC may modulate the morphogenesis and maintenance of tubular/ductal architectures in organs generated from the primary duct system. 50 Several recent studies indicated that FPC is involved in notch-like processing and that its extremely large extracellular domain is released from the primary cilia of renal epithelial cells. 51 That GFP-positive signals were detected at the microvilli of tubular epithelia in our Pkhd1 Ϫ/Ϫ mice agrees with the report that FPC may be released into the tubular/ductal lumen.…”
Section: Discussionmentioning
confidence: 99%